Tacrolimus to Belatacept Conversion Following Hand Transplantation: A Case Report. Issue 8 (13th March 2015) - Cendales, L.; Bray, R.; Gebel, H.; Brewster, L.; Elbein, R.; Farthing, D.; Song, M.; Parker, D.; Stillman, A.; Pearson, T.; Kirk, A. D.
<x xml:space="preserve">Abstract</x> Vascularized composite allotransplantation (VCA) has emerged as a viable limb replacement strategy for selected patients with upper limb amputation. However, allograft rejection has been seen in essentially all reported VCA recipients indicating a requirement for substantial immunosuppressive therapy. Calcineurin inhibitors have served as the centerpiece agent in all reported cases, and CNI‐associated complications associated with the broad therapeutic effects and side effects of calcineurin inhibitors have been similarly common. Recently, belatacept has been approved as a calcineurin inhibitor replacement in kidney transplantation, but to date, its use in VCA has not been reported. Herein, we report on the case of a hand transplant recipient who developed recurrent acute rejection with alloantibody formation and concomitant calcineurin inhibitor nephrotoxicity, all of which resolved upon conversion from a maintenance regimen of tacrolimus, mycophenolate mofetil and steroids to belatacept and sirolimus. This case indicates that belatacept may be a reasonable maintenance immunosuppressive alternative for use in VCA, providing sufficient prophylaxis from rejection with a reduced side effect profile, the latter being particularly relevant for nonlife threatening conditions typically treated by VCA.